The Effect of Delayed Onset Muscle Soreness on Ground Reaction Forces and Loading Rate During Landing - Ali Jalalvand (Beyhagh)
Background and Aims: The link between Delayed onset of muscle soreness (DOMS) and force components and loading rate during landing is not well understood. Therefore, the aim of this study was to investigate the effect of DOMS on ground reaction forces and loading rate during landing in healthy subjects. Materials and Methods: Twelve healthy men participated in this study. A Kistler force plate (1000 Hz) was used to measure of GRFs components during landing. Then, peak and downfall values of GRFs, loading rate, along with time to peak were extracted. Paired t test with significance level was used for statistical analysis (P ˂ 0.05). Result: Delayed onset of muscle soreness does not affect GRFs at heel-contact (P ˂ 0.05). Exercise-induced muscle damage (EIMD) reduces the amplitude of Fz1 (peak GRFs) at Toe-contact (P = 0.038); the amplitude of Fz2 (downfall GRFs) at Toe-contact (P = 0.006). In EIMD conditions, subjects displayed faster time to peak of FZ1, 2(p=.001; p=.010). Conclusion: Exercise-induced muscle damage reduces GRFs at Toe-contact during landing. This may be due to skeletal muscle stiffness following Exercise-induced muscle damage. Faster time to peak at Toe-contact is considered as a risk factor during landing. These altered variables in healthy subjects are the cause of future injuries need to be addressed in further studies